Strongly Anisotropic Strain‐Tunability of Excitons in Exfoliated ZrSe3 (Adv. Mater. 1/2022). Issue 1 (7th January 2022) - Li, Hao; Sanchez‐Santolino, Gabriel; Puebla, Sergio; Frisenda, Riccardo; Al‐Enizi, Abdullah M.; Nafady, Ayman; D'Agosta, Roberto; Castellanos‐Gomez, Andres
Abstract : Strain Engineering In article number 2103571, Roberto D'Agosta, Andres Castellanos‐Gomez, and co‐workers report a method to apply uniaxial strain along different crystal orientations and apply the method to study the strain‐tunability of excitons in zirconium triselenide, a 2D semiconductor with an interesting in‐plane anisotropic crystal structure.